The electro-optic mechanism and infrared switching dynamic of the hybrid multilayer VO2/Al:ZnO heterojunctions - Peng Zhang (Nature Portfolio, 2017)
Abstract Active and widely controllable phase transition optical materials have got rapid applications in energy-efficient electronic devices, field of meta-devices and so on. Here, we report the optical properties of the vanadium dioxide (VO2)/aluminum-doped zinc oxide (Al:ZnO) hybrid n-n type heterojunctions and the corresponding electro-optic performances of the devices. Various structures are fabricated to compare the discrepancy of the optical and electrical characteristics. It was found that the reflectance spectra presents the wheel phenomenon rather than increases monotonically with temperature at near-infrared region range. The strong interference effects was found in the hybrid multilayer heterojunction. In addition, the phase transition temperature decreases with increasing the number of the Al:ZnO layer, which can be ascribed to the electron injection to the VO2 film from the Al:ZnO interface. Affected by the double layer Al:ZnO, the abnormal Raman vibration mode was presented in the insulator region. By adding the external voltage on the Al2O3/Al:ZnO/VO2/Al:ZnO, Al2O3/Al:ZnO/VO2 and Al2O3/VO2/Al:ZnO thin-film devices, the infrared optical spectra of the devices can be real-time manipulated by an external voltage. The main effect of joule heating and assistant effect of electric field are illustrated in this work. It is believed that the results will add a more thorough understanding in the application of the VO2/transparent conductive film device.